2015
DOI: 10.1063/1.4928321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclined magnetic field in flow of third grade fluid with variable thermal conductivity

Abstract: This paper examines effects of inclined magnetic field and heat transfer in the flow of a third-grade fluid by an exponentially stretching surface. Formulation and analysis are given with heat source and sink. Thermal conductivity is taken temperature dependent. The governing boundary layer equations and boundary conditions are simplified through appropriate transformations. Resulting equations are solved for the approximate solutions. Convergence of governed problems is explicitly discussed. Influences of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 36 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…Polyethylene oxides in water, manufacturing oils, slurries, and molten plastics are some of the listed examples of a third‐grade fluid model. The impact of inclined magnetic‐field and heat transfer effects for third‐grade fluid flow by considering exponentially stretching surface geometry have been revealed . Also, Hayat et al explored the outcomes of third‐grade and second‐grade fluid parameters on the flow‐field.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene oxides in water, manufacturing oils, slurries, and molten plastics are some of the listed examples of a third‐grade fluid model. The impact of inclined magnetic‐field and heat transfer effects for third‐grade fluid flow by considering exponentially stretching surface geometry have been revealed . Also, Hayat et al explored the outcomes of third‐grade and second‐grade fluid parameters on the flow‐field.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al [12] presented simulated results for heat and mass transfer in an electrically conducting incompressible nanofluid flow near a heated stretching sheet with a convective boundary condition. The impact of an inclined magnetic field in the flow of a fluid with variable thermal conductivity was studied by Hayat et al [13,14]. An analysis of the significance of a heat source/ sink and temperature dependent thermal conductivity was given.…”
Section: Introductionmentioning
confidence: 99%
“…Hamza et al 21 have examined the MHD convective flow between two vertical walls considering variable thermal conductivity and it was observed that velocity and temperature profiles increase with an enhancement in variable thermal conductivity parameter. Hayat et al 22 have discussed effect of inclined magnetic field in flow of third grade fluid with variable thermal conductivity and heat source/sink. Observations indicate that velocity profile declines with an increase in magnetic field parameter.…”
Section: Introductionmentioning
confidence: 99%